PERAN PENGGUNAAN BSI MOBILE BANKING DALAM KEMUDAHAN BERTRANSAKSI DI ERA SOCIETY 5.0 - Sevya Surya Putri Suwandi; Moh. Rois Abin (Universitas Nusa Cendana, 2023)
This study was conducted to find out the role of BSI Mobile Banking services as a means of convenience in transactions in the era of society 5.0. The method in this study is a descriptive method with a qualitative approach. The object of this research is the people of Pelem village who use BSI Mobile Banking services. This study used primary and secondary data from observations, interviews, and documentation. The technique of testing the validity of the data findings in this study uses triangulation. The results of the study stated that the level of knowledge of the Pelem village community regarding BSI Mobile Banking was good. The decision of the Pelem village community to choose the BSI Mobile Banking feature was on the transfer and payment features which were considered very helpful and could be accessed easily. The benefits felt by the community with the presence of BSI Mobile Banking services are very practical and save time. Keywords: BSI Mobile Banking; Easy Transaction; Society 5.0